Յովհաննէս Թումանեանը Հայաստանի Առաջին Հանրապետութեան հռչակման օրերին - Յովհաննիսեան, Սուսաննա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Ованес Туманян, выдающийся армянский поэт, писатель и общественный деятель, проявил свою патриотическую позицию не только в художественном творчестве, но и в активной гражданской деятельности. Его патриотизм носил конкретный и целенаправленный характер, исключая элементы абстрактного пафоса, мстительности и созерцательности. Важной вехой его общественной деятельности стали события весны 1918 года, в период провозглашения Респу- блики Армения, а также предшествующие этому месяцы. С марта по май 1918 года Туманян находился в Лори, куда он прибыл 25 марта по поручению властей Закавказья, по приглашению местных жителей и по собственной инициативе. Основной целью его миссии было противодействие турецкому военному вторжению и организация обороны региона. В рамках этой деятельности он способствовал вооружению местного населения, привезя с собой боеприпасы, приобретенные при финансовой поддержке и содействии Американского консульства. Hovhannes Tumanyan, a prominent Armenian poet, writer, and public figure, demonstrated his patriotic stance not only through his literary works but also through his active civic engagement. His patriotism was characterized by a concrete and pragmatic approach, devoid of abstract idealism, vengefulness, or excessive rhetoric. A significant phase of his public activity was marked by the events of the spring of 1918, particularly during the proclamation of the Republic of Armenia and the preceding months. From March to May 1918, Tumanyan was in Lori, where he had arrived on March 25 upon the instruction of the Transcaucasian government, at the invitation of the local population, and on his own initiative. His primary objective was to counter the Turkish invasion and to organize the self-defense of the region. In this effort, he facilitated the transportation of arms and ammunition, which were acquired with the financial support and assistance of the American Consulate. Tumanyan’s activities were not limited to military support. He played a key role in interethnic dialogue as the deputy chairman of the newly established Armenian-Muslim Bureau, which aimed to prevent intercommunal conflicts. Additionally, he served as the chairman of the association of twenty compatriotic unions, further solidifying his influence in the region.
Keywords: Պատմութիւն